Assessing chemostratigraphic and biostratigraphic correlation of Ediacaran phosphorites (Bocaina, Khesen and Doushantuo Formations): Diachronic, local signals of the Neoproterozoic phosphogenic-taphonomic event - Hippertt, João Pedro T.M.; Rudnitzki, Isaac D.; Morais, Luana [UNESP]; Freitas, Bernardo T.; Romero, Guilherme R.; Babinski, Marly; Leite, Mariangela G.P.; Leme, Juliana M.; Nalini, Hermínio A.; Nogueira, Leonardo B.; Trindade, Ricardo I.F. (Elsevier, 2024)
The Neoproterozoic phosphogenic event records biotic and biogeochemical changes that seem to indicate intrinsic relationships between phosphogenesis and phosphatic fossil preservation. However, chemo-litho and biostratigraphic correlations conducted on fossiliferous, phosphatic successions of the Doushantuo Formation, South China, evidence a highly heterogeneous record, featuring diachronic depositional ages, variable taxonomic diversity and inconsistent, “noisy” δ13C records. Similar detailed chemo-litho and biostratigraphic correlations targeted in high-grade phosphorite strata have not been performed along Ediacaran units elsewhere. Considering the significance and scarcity of Ediacaran high-grade phosphorite strata, establishing a comprehensive correlation framework within and between those units is fundamental to understanding Ediacaran biogeochemical and biotic evolution. This work aims to integrate new δ13C isotope stratigraphy, and existing Doushantuo-Pertatataka acritarch assemblages and geochronological records from Bocaina (Brazil), Khesen (Mongolia) and Doushantuo (China) Formations. Phosphate rich strata in those units feature inconsistent δ13C signatures characterized by negative values showing large bed-to-bed variations, possibly reflecting local modification of original marine signals by phosphogenesis, suggesting caution against the use in global/regional chemostratigraphic correlation. The record of phosphatized acritarch assemblages shows contrastive taxonomic diversities, and a small number of common taxa including Megasphaera. Whereas the presence of biozonal Doushantuo Formation taxa on Khsesen Fm, resonates with growing views of strong environmental resilience and large temporal ranges of acanthomorph acritarchs throughout the Ediacaran-early Cambrian, the scarcity of similar taxa in the Bocaina Fm may question the reliability of Doushantuo Fm acritarch biozones in other paleogeographic or paleoenvironmental scenarios. Alternatively, the low taxonomic diversity recorded in Bocaina and Khesen Fms may also reflect the effects of the late Ediacaran decline in acritarch diversity. Further, combined evidence of selective paleoenvironmental phosphatization, local geochemical signals, narrow time spans and heterogeneous taxonomic diversity found in phosphatized DPK acanthomorph assemblages indicate the local nature of Ediacaran phosphatic fossil preservation events. Finally, evidence for diachronic preservation between high-grade phosphatic strata and phosphatized microfossils show non-causal relationships between Ediacaran phosphogenesis and phosphatic fossil preservation, highlighting the punctuated, intrinsic local nature of those events.
Keywords: Carbon isotope stratigraphy; Ediacaran; Phosphatic acritarchs; Phosphatic taphonomy; Phosphorite